The Prevalence and Correlates of Falling Down in the Older Adults Over 55 Years in Shiraz - Ali Ghanbary; Nasrin Salehi Dehno; Farzaneh Moslemi Haghighi; Maede Torabi (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Falling down is one of the most common problems that involve old people. It may affect the physical, emotional and social aspects of individual’s health and may cause economical and social problems for individuals and society. Methods & Materials: In a cross sectional study, 750 old people with ages of 55 or more, living in the city of Shiraz (409 female, 341 male, mean ages 67.32 year) with a convenience sampling method took part in this study. A questionnaire was designed to gather the information about the history of falling down on past year, its complications and the possible associated factors. Chi square and Mann_ Witeny test and logistic regression method was used to analyze the study data. Results: the prevalence of falling down was 33.6%. 20.4% of people had single falling down and 13.2% of them had recurrent falling down. There were significant correlations between falling down and age (P=0.016), sex (P<0.001), diabetes (P=0.008), vertigo (P<0.0001). However no significant correlation was found between falling down with arthritis, heart disease, nervous system disease, rheumatologic disease, hypertension and use of cane and glass. There were significant correlation between recurrent falling down and sex (P=0.021), vertigo (P<0.0001) and osteoporosis (P=0.024). Also, use of cane (P=0.023) and arthritis (P=0.048) were associated with falling down with injury. Conclusion: According to results of this study, one third of old people over 55 year living in the community experienced falling down within one year. Diabetes and vertigo increased the risk of falling down in elderly population. Planning for controlling these risk factors can reduce the rate of falling down and its associated problems and complications.